2005
DOI: 10.1111/j.1740-1461.2005.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Not Crisis: Medical Malpractice Claim Outcomes in Texas, 1988–2002

Abstract: Using a comprehensive database of closed claims maintained by the Texas Department of Insurance since 1988, this study provides evidence on a range of issues involving medical malpractice litigation, including claim frequency, payout frequency, payment amounts, defense costs, and jury verdicts. The data present a picture of remarkable stability in most respects and slow, predictable change in others. We find no evidence of the medical malpractice crisis that produced headlines over the last several years and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 20 publications
4
31
1
Order By: Relevance
“…A recent study of malpractice claims, based on evidence from the Texas Department of Insurance, directly contradicts contentions that the sharp increases in insurance rates for medical malpractice in the past decade are the result of jury behavior or a tort crisis (Black et al 2005). The study revealed no increase in the number of claims, no increase in the median or mean pay outs, and no change in the percentage of claims with payments of more than $1 million.…”
Section: Public Perception and Civil Jury Datamentioning
confidence: 87%
“…A recent study of malpractice claims, based on evidence from the Texas Department of Insurance, directly contradicts contentions that the sharp increases in insurance rates for medical malpractice in the past decade are the result of jury behavior or a tort crisis (Black et al 2005). The study revealed no increase in the number of claims, no increase in the median or mean pay outs, and no change in the percentage of claims with payments of more than $1 million.…”
Section: Public Perception and Civil Jury Datamentioning
confidence: 87%
“…There is a widespread perception, especially in the medical community, that malpractice litigation is out of control (Bornstein & Robicheaux, 2008). Although this perception has little basis in fact (e.g., Black, Silver, Hyman, & Sage, 2005), it has been a major impetus for the tort reform movement (Bornstein & Robicheaux, 2008; Halton & McCann, 2004). Moreover, advocates of tort reform place much of the blame for the perceived ills of the civil justice system squarely on the jury (Landsman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that mean time to resolution for pediatrics cases increased significantly over our sample period, consistent with past findings. 4,22 Lengthy time to resolution is an additional cost of medical malpractice that is often not estimated but may be substantial when there is lost practice time and nonmonetary costs to physicians, such as reputational damage and anxiety. 3 Pediatric patients and their families are also adversely affected by delays in compensation and personal closure that are caused by lengthy time to resolution.…”
Section: Discussionmentioning
confidence: 99%